2021
DOI: 10.1088/1755-1315/943/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corporate Water Disclosure on Financial Performance

Abstract: Natural resources crises specifically the water crises are listed in the top ten global risk in 2021. Water demand and withdrawal increase as the population rise. To mitigate water scarcity, companies disclose more on water related information as an engagement to achieve the Sustainable Development Goal (SDG). Motivated towards exploring the impact of corporate water disclosures, this study aims to examine effect corporate water disclosures for five years to financial performance of the sample companies. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Water consumption refers to the amount of water used that is not returned to its original source after being withdrawn. It is recognized as a significant risk, and there are sustainability criteria in place that emphasize efficient water management (Ali et al, 2021). The financial impact of reported water risks in 2020 was substantial, with the cost of mitigation significantly lower than the potential financial impact (Ali et al, 2021).…”
Section: Water Consumption Disclosuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Water consumption refers to the amount of water used that is not returned to its original source after being withdrawn. It is recognized as a significant risk, and there are sustainability criteria in place that emphasize efficient water management (Ali et al, 2021). The financial impact of reported water risks in 2020 was substantial, with the cost of mitigation significantly lower than the potential financial impact (Ali et al, 2021).…”
Section: Water Consumption Disclosuresmentioning
confidence: 99%
“…It is recognized as a significant risk, and there are sustainability criteria in place that emphasize efficient water management (Ali et al, 2021). The financial impact of reported water risks in 2020 was substantial, with the cost of mitigation significantly lower than the potential financial impact (Ali et al, 2021). This has led investors to pay closer attention to corporate disclosures regarding water usage and associated risks (Trausch et al, 2011).…”
Section: Water Consumption Disclosuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Khuong, Anh, et al (2022) and Khuong, Nguyen, et al (2022) found that 170 companies listed on the Ho Chi Minh Stock Exchange responded to water management issues and had a positive impact on their company value. This also applies to companies that are included in the top 50 global market capitalization in increasing earnings per share (EPS) (Ali et al, 2022). Like CSR, which can be affected by corporate risk, systematic risk was found to have a negative effect on water disclosure (Zeng et al, 2020).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…However, the current literature shows that corporate water disclosures still receive little academic attention. Currently, the literature related to water disclosure has focused on the association with the cost of capital (Zhou et al, 2018), the credibility of the information disclosed (Talbot & Barbat, 2020), company risk (Zeng et al, 2020), linkage with CSR (Zhang et al, 2021), financial performance (Ali et al, 2022), firm value (Khuong, Anh, et al, 2022; Khuong, Nguyen, et al, 2022), board diversity (Peng et al, 2022), stakeholder information (Gilsbach et al, 2022; Yu, 2022), and ownership structure (Wicaksono & Setiawan, 2022). In the context of Indonesia, Adhariani (2021) used content analysis to examine water reporting and disclosure requirements, their relationship with political connections and corporate culture (Bambang et al, 2020), as well as the perspective of agenda‐setting theory (Wicaksono et al, 2020).…”
Section: Introductionmentioning
confidence: 99%